Conventional and inverse barocaloric effects around triple points in ferroelastics (NH4)3NbOF6 and (NH4)3TiOF5. (October 2017) - Gorev, M.V.; Bogdanov, E.V.; Flerov, I.N.
Abstract: We report the conventional and inverse barocaloric effect (BCE) in ferroelastics (NH4 )3 NbOF6 and (NH4 )3 TiOF5 . We found a rich set of the structural phase transitions and triple points on the T − p phase diagrams. Extensive and intensive BCE near some transformations and around triple points in both crystals are outstanding (|∆ S BCE max | = 30–100 J/kg·K; |∆ T AD max | = 4–22 K) and can be achieved at low pressure 0.01–0.60 GPa. PACS: 62.50.-p 65.40.-b 81.30.-t Graphical abstract: